2021
DOI: 10.2147/jir.s324232
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adenosine Receptor A2A in the Regulation of Macrophage Exosomes and Vascular Endothelial Cells During Bone Healing

Abstract: Background: Macrophage exosomes and vascular endothelial cells (VECs) are critical to bone healing. However, few studies explore the molecular regulation of them in the bone fracture microenvironment. Methods: In this study, we explored the effects of adenosine receptor A2A (ADA2AR) in macrophage exosomes and VECs during bone healing. CGS21680 (an ADA2AR agonist) and ZM241385 (an ADA2AR antagonist) were used. First, the effects of the ADA2AR on VECs during bone healing were studied in vivo in a rat tibial frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 45 publications
(72 reference statements)
0
22
0
Order By: Relevance
“…Macrophage-MSC communication plays a significant role in maintaining bone homeostasis and promoting bone establishment ( Pieters et al, 2019 ; Chen K. et al, 2020 ; Kang et al, 2020 ; Wang D. et al, 2021 ). Previous studies have confirmed that macrophages communicate with MSC and affect its osteogenic differentiation through exosomes ( Ekstrom et al, 2013 ).…”
Section: Exosomes and Bone Diseasesmentioning
confidence: 99%
“…Macrophage-MSC communication plays a significant role in maintaining bone homeostasis and promoting bone establishment ( Pieters et al, 2019 ; Chen K. et al, 2020 ; Kang et al, 2020 ; Wang D. et al, 2021 ). Previous studies have confirmed that macrophages communicate with MSC and affect its osteogenic differentiation through exosomes ( Ekstrom et al, 2013 ).…”
Section: Exosomes and Bone Diseasesmentioning
confidence: 99%
“…PEMF has been shown to have its actions on several cell types including hematopoietic and skeletal through adenosine A2A receptors as described above and reviewed elsewhere [ 68 ]. Therefore, it is of interest that the activation of A2A receptors is essential for angiogenesis and secretory products of macrophages during bone healing and that the inactivation of adenosine A2A receptors results in both deficient angiogenesis and fracture nonunion [ 76 ].…”
Section: Experimental Differentiation Of Mesenchymal Cells To Chondro...mentioning
confidence: 99%
“…However, ZM241385 (an ADA2AR antagonist) inhibited these functions, thus inhibiting angiogenesis in the early stage of bone healing. It was proved that ADA2AR not only affects VECs but also plays a role in the secretion of M-sEVs during bone healing ( Wang et al, 2021c ). M-sEVs can not only play an important role in fracture healing but also promote recovery during muscle injury.…”
Section: Orthopedic Diseasesmentioning
confidence: 99%